Argument-driven inquiry in biology : lab investigations for grades 9-12 - Sampson, Victor, ....- (Arlington : NSTA Press, 2014)
Are you interested in using argument-driven inquiry for high school lab instruction but just aren t sure how to do it? You aren t alone. This book will provide you with both the information and instructional materials you need to start using this method right away. Argument-Driven Inquiry in Biology is a one-stop source of expertise, advice, and investigations. The book is broken into two basic parts: 1. An introduction to the stages of argument-driven inquiry from question identification, data analysis, and argument development and evaluation to double-blind peer review and report revision. 2. A well-organized series of 27 field-tested labs that cover molecules and organisms, ecosystems, heredity, and biological evolution. The investigations are designed to be more authentic scientific experiences than traditional laboratory activities. They give your students an opportunity to design their own methods, develop models, collect and analyze data, generate arguments, and critique claims and evidence. Because the authors are veteran teachers, they designed Argument-Driven Inquiry in Biology to be easy to use and aligned with today s standards. The labs include reproducible student pages and teacher notes. The investigations will help your students learn the core ideas, crosscutting concepts, and scientific practices found in the Next Generation Science Standards. In addition, they offer ways for students to develop the disciplinary skills outlined in the Common Core State Standards. Many of today s teachers like you want to find new ways to engage students in scientific practices and help students learn more from lab activities. Argument-Driven Inquiry in Biology>/i> does all of this even as it gives students the chance to practice reading, writing, speaking, and using math in the context of science.
Keywords: Natuurwetenschappen -- Secundair onderwijs